Perfis individuais e estilos de aprendizagem em ambiente híbrido: um estudo com professores em formação continuada - Leite, Eliana Alves Moreira (2022)
The social, cultural and technological changes that occur in contemporary society have influenced the teachers’ professional training. The training environments changed with addition of the virtual environment to the on-site one, resulting in hybrid training processes, encompassing professionals from different realities and individual profiles. The heterogeneity of the hybrid training scenario face challenges that emerge from the need to structure training processes, through teacher’s particularities. Thus, this study was grounded on the following research question: Does identifying the primary education teacher's profile and learning style on in-service education in a hybrid environment prospect a personalised didactic-pedagogical design? To answer this question, the following specific objectives were prepared: (i) to describe the elements that contribute to the teachers' in-service education; (ii) to identify the individual profile and learning styles of primary education teachers in in-service education; (iii) to map the appropriate strategies to the individual profiles and learning styles of the primary education teacher in in-service education; (iv) to list the causes for primary education teacher dropout in in-service education in a blended environment; (v) to project a re(design) of in-service education courses for teachers in blended environments. Given the nature of the outlined objectives, a qualitative and quantitative methodology was adopted with a case study design. The research participants were teachers of the specialization course in Environmental Education, offered by a Brazilian Federal University (2017-2019). For data collection, questionnaires and interviews were used, applied during the course and with graduates and the participants' narratives. The characteristics of the profiles and individual styles of teachers were identified from these data, common indicatives corroborated for the course design under analysis, with the perspective of re(design) of hybrid scenarios. It is considered that knowledge about teacher's specificities results in a diagnostic and dialogic training, in which it is permeated by the appreciation of the teacher's opinion about their own training, deconstructing the homogenization and impersonality in the training paths, bringing the awareness of listening to this subject.